2006
DOI: 10.1080/01932690600662679
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior in Confinement Studied with a Surface Force Apparatus

Abstract: The free energy of a surface has a major influence on the phase behavior of systems where the area-to-volume ratio is large. These include finely dispersed solids and liquids as well as substances confined to meso-and microporous solids. In a surface force apparatus (SFA) mica surfaces at or close to contact form a single model pore in which surface energy effects on phase behavior may be conveniently studied. Capillary condensation of liquid from undersaturated vapor is the most familiar example of a surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Data from surface force apparatus measurements also showed that n-alkanes (n $ 8) formed layered structures when conned between silica and mica surfaces whereas thin liquid lms of branched alkanes were much more unstable and were readily expelled from between the two surfaces. [16][17][18][19][20] Again, data were interpreted with "geometric" explanations that considered solvent packing and organization as the primary contributors to liquid behavior at an interface.…”
Section: Introductionmentioning
confidence: 99%
“…Data from surface force apparatus measurements also showed that n-alkanes (n $ 8) formed layered structures when conned between silica and mica surfaces whereas thin liquid lms of branched alkanes were much more unstable and were readily expelled from between the two surfaces. [16][17][18][19][20] Again, data were interpreted with "geometric" explanations that considered solvent packing and organization as the primary contributors to liquid behavior at an interface.…”
Section: Introductionmentioning
confidence: 99%